PENGARUH POLA ASUH ORANG TUA DAN PENGGUNAAN GADGET TERHADAP HASIL BELAJAR MATA PELAJARAN IPS SISWA KELAS VII SMP NEGERI 1 SINGOSARI - Hidayatul M, Fuji Ayu (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Based on the theory of learning outcomes, Clark states that student learning outcomes in schools are 70% influenced by students' abilities and 30% are influenced by the environment. The part of the environment is parents and technology (gadgets). To prove the theory, the purpose of this research is 1. Find out the influence level of parental care on social science learning achievement of Grade VII students in SMPN 1 Singosari, 2. find out the influence level of gadget use on social science learning achievement of Grade VII students in SMPN 1 Singosari, 3. find out the influence level of parental care and gadget use on social science learning achievement of Grade VII students in SMPN 1 Singosari. To achieve the aims, the researcher employed quantitative research using correlational approach. The population consists of 324 students of Grade VII in SMP Negeri 1 Singosariand the researcher took 180 samples out of the population. The data analysis is conducted using classical assumption tests such as normality test, multicollinearity test, heteroscedasticity test and multiple linear regression analysis, determination, t-test and F-test. The results showed that parenting and the use of gadgets simultaneously or simultaneously affect the results of students' eyes IPS student grade VII SMPN 1 Singosari, meaning that the more optimal parent care pattern, bush in the optimal use of the gadgets used properly and parental supervision in the use of gadgets will affect student learning outcomes and student learning outcomes will be better.Keywords: parental care; gadget use; learning outcomes